Analysis Of English Students’ Book For XI Grade Of Tourism Vocational School Students - Ruly Rosmalina; Leny Saili Rahmah (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Textbooks play a crucial role in English language teaching, particularly in vocational schools where materials are expected to support students’ professional and communicative needs. However, many textbooks still provide general English content without sufficient attention to specific vocational contexts. This study aimed to evaluate the English textbook used by eleventh-grade tourism vocational students and to analyze its relevance to learners’ academic and workplace needs. This research employed a descriptive qualitative design using a triangulation of instruments: a textbook evaluation checklist, student questionnaires, and teacher interviews. The data were analyzed thematically and descriptively to identify the strengths and weaknesses of the textbook in relation to the 2013 Curriculum and the requirements of English for Specific Purposes (ESP). The findings revealed that the textbook was only partially aligned with the needs of tourism students. While it covered general language skills, it lacked listening activities, contained insufficient tourism-related vocabulary, and offered limited authentic tasks relevant to the tourism industry. Teachers reported supplementing the textbook with authentic resources to bridge the gap between classroom learning and workplace demands. In conclusion, the study highlights the urgent need for vocational English textbooks that are based on systematic needs analysis and that integrate authentic, domain-specific tasks. It is recommended that future textbook development for vocational schools focus on industry relevance to better prepare students for employability and career success in tourism.